The Development of e-Participation in the Official Public Communications in Ukraine - Fedoniuk, Sergii; Федонюк, Сергій Валентинович (Lesia Ukrainka Volyn National University, 2012)
Displaying the status of implementation of the principles of e-participation in Ukraine in the context of current trends and approaches in european open democracy, associated with the expansion of opportunities for information access and realizing the potential of information and communication technologies in politics.
Розвиток е-участі в офіційній публічній комунікації в Україні
Work is executed on the department of international information of the Volhynia national university of the name of Lesya Ukrainian
Keywords: e-participation; електронна участь; Internet; information and communication technologies; the European Union; Ukraine; Інтернет; інформаційні та комунікаційні технології; Європейський Союз; Україна